2014
DOI: 10.7554/elife.01671
|View full text |Cite
|
Sign up to set email alerts
|

A lipid bound actin meshwork organizes liquid phase separation in model membranes

Abstract: The eukaryotic cell membrane is connected to a dense actin rich cortex. We present FCS and STED experiments showing that dense membrane bound actin networks have severe influence on lipid phase separation. A minimal actin cortex was bound to a supported lipid bilayer via biotinylated lipid streptavidin complexes (pinning sites). In general, actin binding to ternary membranes prevented macroscopic liquid-ordered and liquid-disordered domain formation, even at low temperature. Instead, depending on the type of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(128 citation statements)
references
References 54 publications
12
116
0
Order By: Relevance
“…Finally, most model membranes lack key aspects that are fundamental to cell membrane functions, including but not limited to connection to a dynamic actin cortex and the transport of membrane components via both active and passive mechanisms. Recent progress has begun to address some of these issues 35-37 but the vast divide between model and cell membranes will likely remain a major challenge for bottom-up investigations for decades to come.…”
Section: A Spectrum Of Membrane Modelsmentioning
confidence: 99%
“…Finally, most model membranes lack key aspects that are fundamental to cell membrane functions, including but not limited to connection to a dynamic actin cortex and the transport of membrane components via both active and passive mechanisms. Recent progress has begun to address some of these issues 35-37 but the vast divide between model and cell membranes will likely remain a major challenge for bottom-up investigations for decades to come.…”
Section: A Spectrum Of Membrane Modelsmentioning
confidence: 99%
“…As commented in Sec. I, such distribution has been used to describe the heterogeneities present in plasma membranes [13,14]. In this context, relating P (κ) to such distribution of sizes provides a way to connect spatio-temporal properties of the environment at criticality to the stemming of subdiffusion, and thus offers an analytical tool to study their interplay.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…Besides membrane proteins, the lipids -the most abundant components of the * miguel.garcia-march@icfo.es cell membrane -contribute to this heterogeneous organization by interacting with cholesterol, proteins and the cytoskeleton in order to partition the membrane [11], as a consequence of these dynamic interactions, also lipids exhibit non-Brownian diffusion behavior [12]. Due to the presence of miscibility critical points and associated long-range critical fluctuations, the compositional heterogeneity of the plasma membranes has been often modeled as a nearly critical environment through an Ising model [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Such a reorganization of the actin meshwork would be associated with reduced receptor mobility. Using FCS and STED it was recently shown that membrane-bound actin networks influence lipid phase separation; a model combining the coupling of membrane composition, membrane curvature, and the actin pinning sites was postulated from this study (Honigmann et al, 2014). More recently, confocal FRAP distinguished two protein populations of membrane proteins, including some classical “synaptic” proteins in PC12 cells, having diffusion coefficients D of 0.22 and 0.01 μm 2 s -1 , respectively (Saka et al, 2014).…”
Section: Effect Of Cholesterol On Nachr Translational Mobilitymentioning
confidence: 78%
“…There is evidence of interactions between lipids, lipid domains and the cytoskeleton (Maxfield, 2002; Lenne et al, 2006; Honigmann et al, 2014). According to Kwik et al (2003) cholesterol depletion produces general effects on the architecture and function of the membrane, making the sub-membrane cytoskeleton and in particular the cortical actin network more stable.…”
Section: Effect Of Cholesterol On Nachr Translational Mobilitymentioning
confidence: 99%